Polish Reception of Alexander Blok in the Russian Press of the Interwar Wilno - Лавринец, Павел (Literatūra, 2022)
The Russian press of interwar Wilno reflected Polish translations of the poetry of Alexander Blok and the opinions of Polish critics about the work of the Russian poet. These reflections were accompanied by publications with remarks about Blok’s influence on Polish poets. The study of articles and notes on such topics reveals the literary landmarks of the Wilno Russian environment, the mechanisms for the formation and strengthening of the literary reputation of the Russian poet. The research materials are extracted from the Wilno press in Russian in 1923–1934. The study showed that the Polish reception of Blok’s work helped to strengthen the literary reputation of the greatest Russian poet of the era.